2015
DOI: 10.15644/asc49/2/7
|View full text |Cite
|
Sign up to set email alerts
|

New Knowledge about Zirconium-Ceramic as a Structural Material in Fixed Prosthodontics

Abstract: Dental ceramics represents a major structural material in fixed prosthodontics. Increasing demands for esthetics led to development of new ceramic materials in order to eliminate the use of metal framework and for all ceramic restorations with mechanical properties to withstand high occlusal forces. Out of all the present ceramic materials, zirconium-ceramic has the best mechanical properties, and is the only material that can be used for longer span fixed dental restorations. Despite its excellent mechanical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 30 publications
0
12
0
1
Order By: Relevance
“…6 Laboratory studies have shown that zirconia checks all the boxes and is becoming the main choice as a restorative material for dentists across the world. 4 Currently there are two different types of Y-TZP attachments available, a ball attachment for overdentures as a part of zirconia post and an extracoronal, cylindrical, or ball attachment for removable partial dentures. 3 However there is no literature available regarding either clinical performance or effectiveness.…”
Section: Figs 1a To E: Procedural Steps In Casementioning
confidence: 99%
“…6 Laboratory studies have shown that zirconia checks all the boxes and is becoming the main choice as a restorative material for dentists across the world. 4 Currently there are two different types of Y-TZP attachments available, a ball attachment for overdentures as a part of zirconia post and an extracoronal, cylindrical, or ball attachment for removable partial dentures. 3 However there is no literature available regarding either clinical performance or effectiveness.…”
Section: Figs 1a To E: Procedural Steps In Casementioning
confidence: 99%
“…The drawback of the zirconia post is that the high elastic modulus causes stress that can lead to root fracture. 42,[45][46][47][48] The sealing ability of zirconia post systems compared with that of other systems has been evaluated by different studies. Mitov et al 49 reported that zirconia provides the same level of coronal sealing to that of fiber post and titanium post systems.…”
Section: Zirconia Postmentioning
confidence: 99%
“…Osim povoljne kemijske stabilnosti, dobre estetike i fizikalnih svojstava (12), keramika izrađena od cirkonija ima i odličnu radiokontrastnost, visoku provodljivost svjetla (13) i modul elastičnosti sličan metalnom kolčiću (14). Ipak, visoki modul elastičnosti od 200 GPa uzrokuje prenošenje stresa na manje kruti dentin, što rezultira lomom zubnog korijena (15).…”
Section: Fiber Reinforced Postsunclassified
“…Apart from its favorable chemical stability, good esthetic and physical properties (12), zirconia also yields excellent radiographic opacity, superior light transmission properties (13) and Young's modulus similar to that of the stainless steel alloy (14). However, the high elastic modulus of zirconia posts at 200 GPa causes stress to be transferred to the less rigid dentin, thereby resulting in root fractures (15).…”
mentioning
confidence: 99%